Stratification of the risk of developing tardive drug-induced complications - L. A. Khublarova; D. V. Zakharov; V. A. Mikhaylov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Tardive drug dystonia / dyskinesia is one of the rare, and at the same time, the most severe motor complications associated with the use of pharmacological drugs. Complex assessment of risk factors for the development of tardive drug-induced side effects makes it possible to take a more rational approach for the target therapy, to make rehabilitation more effective and safe.